(untitled) (BIRDEM Medical Journal, 2017)
Tuberous sclerosis is a disorder affecting multiple organs leading to morbidity and mortality. It is important to make an early diagnosis of tuberous sclerosis so that lifelong monitoring, early recognition of complications and proactive treatment can lower the morbidity and mortality rates. Here we report a case of a 50-year-old male who presented with seizure. This case report emphasizes the importance of complete evaluation of a case presenting with seizures. Tuberous sclerosis must be included in the differentials if patient presents with seizures, skin manifestations and mental retardation. Birdem Med J 2016; 6(2): 127-129